2019
DOI: 10.1088/1757-899x/599/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Studies of Zinc doped BiFeO3 on the Bi-site

Abstract: Zinc-doped bismuth ferrite (Bi1-x Zn x FeO3, x = 0, 0.05, 0.1) powdered were synthesized through sol-gel auto combustion methods to investigate the optical properties while maintaining the whole structure of BiFeO3 (BFO). The Zn doped induced the reveal of Bi25FeO40 as a secondary phase and decreased the bond angle of Bi–O–Fe in the BFO phase structure which affect the electron density formation inside of the lattice. The presence of Zn content has also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…[18] While a multitude of synthesis routes have been considered, it still remains difficult to achieve pure phase and avoid the appearance of parasitic phases because of doping. [16][17][18][19][20][21][22] The novelty of the reported work involves the synthesis of Zn-doped BFO nanoparticles with an average grain size of 8 nm using hydrothermal synthesis. The successful substitution of Fe ion by larger size ions like Zn in high-quality BFO increases distortion affecting the crystal formation and oxygen vacancies.…”
Section: Doi: 101002/pssr202200081mentioning
confidence: 99%
See 2 more Smart Citations
“…[18] While a multitude of synthesis routes have been considered, it still remains difficult to achieve pure phase and avoid the appearance of parasitic phases because of doping. [16][17][18][19][20][21][22] The novelty of the reported work involves the synthesis of Zn-doped BFO nanoparticles with an average grain size of 8 nm using hydrothermal synthesis. The successful substitution of Fe ion by larger size ions like Zn in high-quality BFO increases distortion affecting the crystal formation and oxygen vacancies.…”
Section: Doi: 101002/pssr202200081mentioning
confidence: 99%
“…[ 16 ] Billah et al reported that Li‐doped on Fe‐site in bulk BFO, synthesized by a conventional solid‐state reaction technique and ultrasonication technique, absorb in UV–vis wavelength region with both a red‐shift and blue‐shift. [ 16 ] As a consequence of the band structure modification, especially the gap value decreases, the photoinduction response can mainly be improved to make BFO more interesting for application. For example, Nadeem et al reported that by Ni substitution the photocatalytic activity of BFO for methylene blue (MB) dye degradation under visible light irradiation has been increased significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38][39] Moreover, the current sol-gel auto-ignition method is time and energy-consuming because it required up to 12 hours to produce a fine powder of pure bismuth ferrite. [40][41][42] However, several studies described the auto-combustion route to synthesize bismuth ferrite, [14,28,[40][41][42][43] but it is rare to find collective studies on the effect of a diverse chelating agent on physicochemical properties of bismuth ferrite nanoparticles. Sharif, Muhammad Kashif, et al [15] used simple auto combustion route to fabricate a series of BiFe 1-x Hf (3/4)x O 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Since some of the chelating agents and solvents in the sol‐gel process lead to secondary phases such as Bi 2 O 3 , Bi 2 Fe 4 O 9 , Bi 25 FeO 40 , the choice of a chelating agent, and solvent plays an essential role in the formation of phase‐pure BFO [36–39] . Moreover, the current sol‐gel auto‐ignition method is time and energy‐consuming because it required up to 12 hours to produce a fine powder of pure bismuth ferrite [40–42] . However, several studies described the auto‐combustion route to synthesize bismuth ferrite, [14,28, 40–43] but it is rare to find collective studies on the effect of a diverse chelating agent on physicochemical properties of bismuth ferrite nanoparticles.…”
Section: Introductionmentioning
confidence: 99%